Communication—Ligand-Dependent Electrochemical Activity for Mn2+ in Lithium-Ion Electrolyte Solutions. Issue 10 (27th June 2019) - Tornheim, Adam; Kirner, Joel; Sahore, Ritu; Lau, Ka-Cheong; O'Hanlon, Daniel C.; Dose, Wesley M.; Lee, Chang-Wook; Liao, Chen; Zhang, Zhengcheng; Balasubramanian, Mahalingam; Croy, Jason R.
Abstract : Manganese dissolution from metal-oxide cathodes, and subsequent deposition at graphitic anodes, are considered to be key causes of capacity fade in lithium-ion batteries. The Mn 2+ redox state is thought to be the major solvated Mn species, but its coordination environment is not well understood. Herein, we present the effects of Mn 2+ -containing electrolytes (Mn(PF6 )2 and Mn(TFSI)2 ) on the performance of lithium-iron-phosphate//graphite (LFP//Gr) cells. Clear differences in first-cycle capacities and subsequent cycling efficiencies depending on the associated counter-ion indicate that the Mn coordination environment has a profound effect on the associated electrochemical degradation mechanisms.